Thoroughly review the recent progresses in improving O/W interfacial properties of proteins through various strategies - Zhang, Haozhen; Zhao, Xue; Chen, Xing; Xu, Xinglian (Frontiers in Nutrition, 2022)
Along with the future food market developing world widely, the personalized nutrition and rational function food design are found to be urgently attracted. Oil in a water (O/W) emulsion system has an excellent ability to maintain nutraceuticals and thus plays a promising role in producing future functional foods. Understanding the interfacial related mechanisms involved are essential for improving the quality of food products. Protein can effectively reduce interfacial tension and stable immiscible phases. The interfacial properties of proteins directly affect the emulsion qualities, which have gradually become a prospective topic. This review will first briefly discuss the interfacial-related fundamental factors of proteins. Next, the paper thoroughly overviewed current physical and chemical strategies tailored to improving the interfacial and emulsion properties of proteins. To be summarized, a higher flexibility could allow protein to be more easily unfolded and adsorbed onto the interface but could also possibly form a softer interfacial film. Several physical strategies, such as thermal, ultrasound and especially high-pressure homogenization are well applied to improve the interfacial properties. The interfacial behavior is also altered by various green chemical strategies, such as pH adjustment, covalent modification, and low molecular weight (LMW) surfactant addition. These strategies upgraded emulsion properties by increasing adsorption load, accelerating diffusion and adsorption rate, associated with lowering interfacial tension, and promoting interfacial protein interactions. Future researches targeted at elucidating interfacial-bulk protein interactions, unraveling interfacial behavior through in silico tools, exploring connection between interfacial-industrial processing properties, and clarifying the interfacial-sensory-digestive relationships of O/W emulsions is needed to develop emulsion applications.